2022
DOI: 10.3390/ma15175977
|View full text |Cite
|
Sign up to set email alerts
|

Flame Retardancy and Thermal Property of Environment-Friendly Poly(lactic acid) Composites Based on Banana Peel Powder

Abstract: Banana peel powder (BPP) was used to prepare poly(lactic acid) (PLA) bio-based composites and the flame retardancy was enhanced by introducing silica-gel microencapsulated ammonium polyphosphate (MCAPP). The results showed that the limiting oxygen index (LOI) of PLA containing 15 wt % BPP was 22.1% and just passed the UL-94 V-2 rate. Moreover, with the introduction of 5 wt % MCAPP and 15 wt % BPP, the PLA composite had a higher LOI value of 31.5%, and reached the UL-94 V-0 rating, with self-extinguishing and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…This decrease was ascribed to the decomposition of hemicellulose structure in the QP powder additive. 45
Figure 5.TGA thermogram of PLA/QP powder composites.
…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This decrease was ascribed to the decomposition of hemicellulose structure in the QP powder additive. 45
Figure 5.TGA thermogram of PLA/QP powder composites.
…”
Section: Resultsmentioning
confidence: 99%
“…It is seen from the thermograms that the percentage of volatile content is quite low compared to the total mass. 45 According to the data obtained from the thermogram of the pure QP powder additive, since the decomposition temperature of this additive is in the range of 170 °C-250°C, it has been observed that a degradation occurs at these temperatures in proportion to the increasing QP ratio in the powder composites. Similarly, the thermal degradation behavior that can be observed from the thermogram of the pure PLA polymer was also observed in the composite structures in a manner consistent with the additive and polymer ratios.…”
Section: Thermogravimetric Analysismentioning
confidence: 99%
“…PLA. BPP can be used as a filler in flame-retardant PLA composites, according to a study by Kong et al [73]. The composites were created using 5 wt% microencapsulated ammonium polyphosphate (MCAPP) and 15 wt% BPP.…”
Section: Banana Peel Powder (Bpp)mentioning
confidence: 99%